2008
DOI: 10.1111/j.1365-4632.2008.03517.x
|View full text |Cite
|
Sign up to set email alerts
|

The successful use of botulinum toxin for the treatment of nasal hyperhidrosis

Abstract: This treatment method for nasal hyperhidrosis is simple, well tolerated, and effective, and significantly improves the quality of life of the affected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A dose of 1 to 2 units per injection spaced every 0.5 to 1.0 cm, for a total dose of 10 to 20 units of ona-BoNT-A, is usually required. 11,12 Take care to avoid the lacrimal system and the nasal muscles when injecting at the lateral nasal wall, keeping injections as medial as possible. Very small aliquots should be injected superficially to help avoid muscle effects.…”
Section: Craniofacial Hyperhidrosismentioning
confidence: 99%
“…A dose of 1 to 2 units per injection spaced every 0.5 to 1.0 cm, for a total dose of 10 to 20 units of ona-BoNT-A, is usually required. 11,12 Take care to avoid the lacrimal system and the nasal muscles when injecting at the lateral nasal wall, keeping injections as medial as possible. Very small aliquots should be injected superficially to help avoid muscle effects.…”
Section: Craniofacial Hyperhidrosismentioning
confidence: 99%
“…Thus, given this distance of 2 cm between injection sites, there is generally no need to make more than nine injections into the nose (Fig. 1), rather than the 20 described in the earlier article 1 . This eliminates the need for 11 painful injections.…”
mentioning
confidence: 95%
“…We refer to an article published in this journal in 2008 by Geddoa et al. 1 on the treatment of nasal hyperhidrosis with botulinum toxin type A and wish to propose some factors that should be considered with reference to the level of comfort experienced by the patient. Because the nose does not represent a large area of skin and as injections in this area are extremely painful, we have identified some methods of improving the technique described in 2008 1 …”
mentioning
confidence: 99%
“…The DLQI was used in studies to measure quality of life on various areas of the body; studies of axillary sweating combined with other parts of the body, such as palms or feet, were most common (n = 26 54,56,69,77,101,103,106,107,114,[119][120][121]139,147,158,170,173,176,214,221,223,263,266,273,274 ). Studies were identified of the palm or palm and foot combined (n = 11 61,128,208,222,230,264,265,[269][270][271][272] ) and of other combinations including the face, palm and/or foot or generalised hyperhidrosis (n = 11 116,117,210,217,227,232,261,262,267,268,275 ).…”
Section: Review Of Quality-of-life Measures/toolsmentioning
confidence: 99%
“…The DLQI was identified in studies conducted globally, including in the UK (n = 9 103,232,261,262,267,268,275 ), the USA and Canada (n = 8 77,107,139,173,176,208,222,263 ), Italy (n = 7 101,102,106,214,223,266,272 ), Germany (n = 5 69,158,227,270,271 ), Sweden (n = 4 114,116,117,128 ), Greece (n = 3 [119][120][121] ), Ireland (n = 2 265,274 ), Iran (n = 2 170,264 ), Spain (n = 2 210,230 ), Australia (n = 1 ) or surgical reviews or reviews of surgery compared with dermatology (n = 3 147,267,273 ). The DLQI was used in studies to measure quality of life on various areas of the body; studies of axillary sweating combined with other parts of the body, such as palms or feet, were most common (n = 26 54,56,69,77,101,103,106,107,…”
Section: Review Of Quality-of-life Measures/toolsmentioning
confidence: 99%